Nonmelanoma Skin Cancer in the Heart of the Middle East: Analysis of Mohs Micrographic Surgery Cases From a Tertiary Care Center in Lebanon - Ahmad Berjawi; Namir Saade; Zeina Tannous (Journal of Skin Cancer)
Skin cancer is the most common cancer worldwide. According to the Skin Cancer Foundation, Mohs micrographic surgery (MMS) is considered the most effective technique for treating nonmelanoma skin cancer (NMSC). Recurrence rate after MMS for treating NMSC ranges from 1.4% to 3.2% for primary tumors and 2.4%–6% for recurrent tumors. The aim of the study was to report data from a tertiary care center in Lebanon providing MMS to patients with NMSC. Retrospective cohort study was conducted through chart review of 94 patients at the Lebanese American University Medical Center (LAUMC-RH) with a total of 115 cases of MMS identified. The study showed that most cases were males (72; 63%), and 77% were aged > 60 years (88). The average tumor size was 1.6 cm. Recurrence rate was zero in primary tumors and 0.9% in recurrent tumors. With respect to age, bivariate analysis showed that cases of males over 60 years of age were more significantly associated with undergoing Mohs surgery (69% vs. 31%; p=0.012). With respect to maximum tumor diameter (MTD) > 1 cm, male gender was associated with a higher MTD when compared to females (74% vs. 26%; p=0.02). Also, Area L was associated with a larger MTD when compared to areas H and M, respectively (90% vs. 61.1% vs. 37.7%; p=0.01). Multivariate analysis of MTD showed that tumors with MTD > 1 cm were significantly associated with male gender, presence in low- or middle-risk areas and being a recurrent tumor. This study shows that MMS is adequate for the treatment of NMSC at our center with minimal complications (< 1%) and recurrence (< 1%).